MICA COMPOSITION REFLECTING CONDITIONS OF AILLIKITE FORMATION IN ZIMA COMPLEX OF EASTERN SIBERIA - V. B. Savelyeva; Yu. V. Danilova; E. P. Bazarova; B. S. Danilov; E. A. Khromova (Геодинамика и тектонофизика, 2024)
Four types of mica were identified in the macrocryst and fine porphyry aillikites from the Yarma zone of the Urik-Ija graben considering specific features of morphology, chemical composition, zonation and crystallization conditions. Mica of the first type was found in macrocryst aillikites. It is available as deformed phlogopite macrocrysts rich in TiO2 (2.5–5.7 wt. %) with varying content of Cr2O3 (from detection limit to 2.0 wt. %) and Mg# 0.87–0.89 and 0.79–0.81 in different dikes. In chemical composition this phlogopite corresponds to the secondary phlogopite from mantle xenoliths, and it was obviously captured by protoaillikite melt form the rocks of the lithosphere mantle. Mica of type 2 represents phlogopite from groundmass and infrequent phenocrysts in fine porphyry aillikites and groundmass of macrocryst aillikites. In this phlogopite, TiO2 content varies in different dikes from 0.7 to 6.0 wt. %, Mg# index varies from 0.70 to 0.90. Phlogopite crystallized within the upper crust at temperature ranging from 840 to 680 °С. Mica of type 3 represents biotite (Mg# 0.40–0.65), producing rims around phlogopite and independent grains in fine porphyry and in places in macrocryst aillikites. The rims crystallized from residual Fe-rich melt at moderately heightened fO2, the temperature of biotite formation reached 700‒760 °C. Mica of type 4 is available in macrocryst aillikites as biotite (Mg# 0.40‒0.67) with phlogopite rims. It was inferred, that this biotite crystallized in intermediate magmatic chambers in the upper crust from essentially carbonate melts, separated through crystallization differentiation from protoaillikite magmas and captured by new portions of less differentiated melts. Obtained data point to metasomatic transformation of the lithosphere mantle, preceding to protoaillikite melting, under the southern margin of the Siberian craton. Thus, we may assume existence in the upper crust of the sites composed of partially crystallized melt.